1966
DOI: 10.1246/bcsj.39.608
|View full text |Cite
|
Sign up to set email alerts
|

The Dipole Moments of the Oligether of Ethylene Glycol

Abstract: The dipole moments of ethylene glycol dimethyl ether (N=1), diethylene glycol dimethyl ether (N=2), triethylene glycol dimethyl ether (N=3), and tetraethylene glycol dimethyl ether calculated on the assumptions that: (i) the dipole moments of these chain molecules are given by the vector sum of the polar groups of ether whose group moment is 1.20 D, and (ii) all the internal rotations of a chain molecule are free. The calculated values of N= 1, N= 2, N=3, and N=4 are 1.67D, 2.03D, 2.33D, and 2.60D, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

1973
1973
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 4 publications
2
12
0
Order By: Relevance
“…The values thus obtained and the value of l g are in table 9. This value matches one of those indicated in [38] where l g was determined in dilution of n-hexane and benzene.…”
Section: Tetraglymesupporting
confidence: 90%
“…The values thus obtained and the value of l g are in table 9. This value matches one of those indicated in [38] where l g was determined in dilution of n-hexane and benzene.…”
Section: Tetraglymesupporting
confidence: 90%
“…triglyme and tetraglyme) and crown ethers (e.g. 18-crown-6, 15-crown-5 and 12-crown-4) in H 2 O and D 2 O; their results suggest that the hydration of crown ethers increases with their size and is predominated by the hydrophobic hydration of -CH 2groups; they also indicate that there is a subtle difference between the hydration of the -CH 2 CH 2 O-group in crown and straight-chain compounds, and the compressibility data reveal a more negative compressibility due to the addition of a -CH 2 CH 2 O-group to crown 23 Heat capacity at 25 C (J mol À1 K À1 ) E T (30), kcal mol À1 E N T Monoglyme 1.62, 75 1.61, 57 1.59, 76 1.71 (in benzene) 76 7.18, 77 7.20, 72 7.55 78 38.2 0.231 191.14 79…”
Section: General Propertiesmentioning
confidence: 99%
“…It is also observed that the internal pressure values of TEGDME are greater than those of heptane and, as expected, they increase with the mole fraction of TEGDME, ranging from 224 MPa for pure heptane at 343.15 K and 1 MPa to 337 MPa for pure TEGDME at 283.15 K and 20 MPa. This is due to the presence of the polar group (µ ) 2.4 D for TEGDME, 35 while µ is close to 0 for heptane 36 ). This behavior has also been found in a previous work for other mixtures.…”
Section: Resultsmentioning
confidence: 93%